Development and assimilate partitioning in Glycine max grown under four light flux densities - Melges, Elena; Lopes, Nei F.; Oliva, Marco A. (Pesquisa Agropecuaria Brasileira, 2014)
Development and assimilate partitioning were studied in Glycine max (L.) Merr. cv. UFV-2 under tour light levels (30, 50, 70 and 100% of sunlight) in field conditions. Irrespective of light flux densities, the maximum number of leaves and maximum height of the plants were attained at the onset of grain filling. Stem elongation increased and the number of leaves and pods were reduced by decreasing light levels. Shading altered the assimilate partitioning among parts but did not change the sequential order of the preferential sinks. The dry matter rates of each organ increased as the light flux densities increased. The rates of root dry matter were more affected by shading than the rates of dry matter production of the other organs.